2021
DOI: 10.1186/s12935-021-01847-6
|View full text |Cite|
|
Sign up to set email alerts
|

Silenced lncRNA DDX11-AS1 or up-regulated microRNA-34a-3p inhibits malignant phenotypes of hepatocellular carcinoma cells via suppression of TRAF5

Abstract: Background Studies have discussed long noncoding RNA DDX11-AS1 (DDX11-AS1)-mediated downstream mechanism in hepatocellular carcinoma (HCC). The goal of this study was to investigate the regulatory mechanism of DDX11-AS1-mediated microRNA-34a-3p (miR-34a-3p)/tumor necrosis factor receptor-associated factor 5 (TRAF5) axis on HCC cells. Methods DDX11-AS1, miR-34a-3p and TRAF5 expression levels in HCC were detected. The correlation of DDX11-AS1, miR-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Consistent with above, Ding G etc. concluded that knock out of DDX11-AS1 or upregulation of miR-34a-3p was key to inhibiting hepatocellular carcinoma cells growth 40 . It has been demonstrated that MIR34AHG might provide new insight to identify potential diagnostic biomarkers and predict the prognosis of lung adenocarcinoma 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with above, Ding G etc. concluded that knock out of DDX11-AS1 or upregulation of miR-34a-3p was key to inhibiting hepatocellular carcinoma cells growth 40 . It has been demonstrated that MIR34AHG might provide new insight to identify potential diagnostic biomarkers and predict the prognosis of lung adenocarcinoma 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…DDX11-AS1 is a newly discovered LncRNA, which is abnormally highly expressed in multiple malignant tumors [ 57 ], such as HCC, colorectal cancer, and gastric cancer. DDX11-AS1 plays its carcinogenic role by regulating the expression of related genes directly or indirectly, with the following examples given: DDX11-AS1 can bind to HNRNPC to promote the proliferation and migration of glioma cells [ 58 ] and silencing DDX11-AS1 can inhibit the growth of HCC cells by upregulating TRAF5 [ 59 ]. These results have suggested that DDX11-AS1 may play a significant regulatory role in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This study for the first time identified that LIN28A was a target of DDX11-AS1 and was involved in DDX11-AS1-mediated drug resistance in BRCA. It has been found that the main mechanism that DDX11-AS1 promotes cancer progression was to eliminate the inhibitory effect of endogenous miRNAs [30][31][32][33]. Few studies have also found that DDX11-AS1 can exert biological functions by interacting with specific proteins.…”
Section: Discussionmentioning
confidence: 99%